Correlation of antibodies against desmogleins 1 and 3 with indirect immunofluorescence and disease status in a Greek population with pemphigus vulgaris. (5th January 2012) - Avgerinou, G.; Papafragkaki, D.‐K.; Nasiopoulou, A.; Markantoni, V.; Arapaki, A.; Servitzoglou, M.; Katsambas, A.; Stavropoulos, P.G.
Abstract Background The use of ELISA testing of antibodies to desmogleins 1 and 3 (anti‐Dsg1 and anti‐Dsg3) and indirect immunofluorescence (IIF) has been strongly supported for the serologic diagnosis of pemphigus. The purpose of this study was to correlate anti‐Dsg1 and anti‐Dsg3 with IIF values, disease localization, treatment and clinical course in Greek patients with pemphigus vulgaris (PV). Methods A total of 54 patients with PV had ELISA serum testing for the presence and titers of anti‐Dsg1, anti‐Dsg3 and IIF. Anti‐Dsg1, anti‐Dsg3 and IIF were correlated with treatment and disease localization. For 40 patients, titers of anti‐Dsg1 and anti‐Dsg3 were assessed in relation to treatment and clinical course after 12 months. Results Anti‐Dsg3 and anti‐Dsg1 positivity in patients with negative IIF was 70.6% and 58.8%, respectively. Anti‐Dsg1 and anti‐Dsg3 were positive in 89.3% and 100% of patients with mucocutaneous disease, respectively, 88.9% and 66.7% of patients with skin limited disease, respectively and 52.9% and 76.5% of patients with mucosal limited disease, respectively. Both antibody titers showed significant correlation with IIF and treatment status. Improvement of clinical status was associated with significant decrease of both anti‐Dsg1 and anti‐Dsg3 after 12 months. Conclusions Serum testing of anti‐Dsg1 and anti‐Dsg3 in PV patients not only provides significant correlations with IIF, treatment and disease type, but may serve as a monitoring tool for clinical course and treatment guidance.